Religious ethics on industrialization: a discourse from Islamic perspective - Zainan Nazri, Mohd Khairul Nizam; Ahmad, Mahmud; Zainan Nazri, Nurul Jannah; Mat Ishak, Mardiana; Sidik, Mohd Akmal; Mohd Hambali, Khadijah (IDOSI, 2012)
This study looks at the religious teaching, which apparently give a full meaning and ethics on industrialization. Islam encourages industrialization and sets its pristine teachings as enshrined in the Quran and Sunnah of the Prophet PBUH as the guiding principles and values for Muslims to create a kind of industrialization that shall bring about not only economic prosperity and sustainable development to the nation, but also one that is in harmony with the environment. The main objectives of this research are to investigate Quranic point of view about the industrialization and relate it to both Western and Islamic perspectives. Its main emphasis is to identify the driving philosophy behind the process of industrialization implemented in Malaysia with the universal values and teachings of Islam. This research is conducted through primarily of historical approach and relies on library research in order to achieve its objectives. A textual and critical analysis of Quranic verses will be utilized to demonstrate the application of Quran pertaining industrialization. Apart from that, this study will attempt to present the concept of industrialization from the Quranic point of view with special reference to selected Quranic verses. The ideas presented could be further developed and appreciated by the society in promoting sustainability environment in this industrialization era